The effect of rotation speed of XP-endo Shaper on apically extruded debris during endodontic procedures : an in vitro study = El efecto de la velocidad de rotación de XP-endo Shaper sobre los desechos extruídos apicalmente durante los procedimientos de endodoncia : un estudio in vitro - Yılmaz, Koray
The aim of this study was to evaluate the effect of using a higher rotation speed with the XP-endo Shaper (XPS) on apically extruded debris and operation time during endodontic treatment and retreatment procedures. Sixty mesial roots of mandibular first molar teeth were randomly assigned to four groups (Initial treatment groups: XPS used at 1000 or 3000rpm rotation speeds and Retreatment groups: XPS used at 1000 or 3000rpm rotation speeds). During the initial treatment and retreatment procedures preweighed eppendorf tubes were used to collect apically extruded debris, and the operation time was recorded in seconds. The extruded debris was quantified by subtracting the preinstrumentation from the postinstrumentation weight of the Eppendorf tubes. Data were analysed using two-way ANOVA at a significance level of 0.05. In all groups, the use of the XPS at 1000 or 3000rpm rotation speeds had no statistically significant effect on the amount of apically extruded debris (p>0.05). The use of the XPS at a 3000rpm rotation speed significantly decreased the instrumentation time (p<0.05). In summary, the use of the XPS at high rotation speeds in initial treatment and retreatment procedures did not have a significant effect on the amount of apically extruded debris but significantly decreased the operation time.